Mengembangkan Kemampuam Kreativitas Melalui Teknik Mozaik pada Anak Kelompok B di TK Negeri 02 Pringgabaya Tahun Ajaran 2021/2022 - Yulia Era Fazira; Nurhasanah Nurhasanah; Baik Nilawati Astini; Ika Rachmayani (Indonesian Publication Center, 2022)
The lack of interesting learning activities to develop creativity in children in TK Negeri 02 Pringgabaya, so the purpose of this research is to develop creativity through activities using mosaic techniques for group B children in TK 02 Pringgabaya, Pringgabaya sub-district for the 2020/2021 academic year. The type of research used is development research. The subjects of this study were the children of group B1 TK Negeri 02 Pringgabaya. The method of data collection in this study used the method of observation, documentation. The data analysis technique in this research is descriptive qualitative. The results of research activities using the mosaic technique to increase the creativity of children in group B1 showed that the average creativity of children increased, namely in the first development 47%, then in the second development 68%, and the third development 91%. The conclusion is that the use of mosaic techniques in learning activities can increase the creativity of group B1 TK Negeri 02 Pringgabaya children.